Kemampuan Menulis Karya Ilmiah Menggunakan Model Berbasis Masalah Peserta Didik Kelas XI SMA Swasta Plus Setia Kabupaten Kepulauan Mentawai - Jamal Mirdad; Dwi Mutia Chan; Yefrizon (JURNAL ARMADA PENDIDIKAN, 2024)
Based on the results of observations and interviews conducted, it was found that the ability to write scientific papers of Class XI students at Plus Setia Private High School, Mentawai Islands Regency is still low. This is evident from the average score obtained by students in writing scientific papers is only 68.96. This score does not meet the minimum completion standard for basic competencies, namely 80. Thus, the Class. The causes of the low scientific writing skills of students in Class , (4) obstacles related to technical matters in writing, namely lack of mastery of Enhanced Spelling, including the use of punctuation, spelling, non-standard standard words, and the systematics of writing good and correct scientific papers. This situation makes researchers interested in finding a solution to this problem. The solution offered by researchers to improve the low average score of scientific writing skills for Class XI Plus Setia Private High School, Mentawai Islands Regency is by using a problem-based learning model assisted by student worksheets. The research results show that the problem-based learning model assisted by student worksheets can be used to improve the ability to write scientific papers in Class XI students at Plus Setia Private High School, Mentawai Islands Regency and can change negative behavior into positive. The increase in test results is in line with changes in student behavior during the learning process of writing scientific papers through a problem-based learning model assisted by student worksheets. This is proven by the results of the analysis of observation sheets which show the results of the analysis of Class XI observation sheets at Plus Setia Private High School, Mentawai Islands Regency.